(untitled) (TAMADDUN NURI JURNALI, 2024)
This article provides an overview of the historical works of Ogahi, in particular the role of zoonyms in the creation of the artistic representation in “Riyozu-d-davla”, the expression and use of words with the meaning of lion in different languages in the work, and the poetic means created with the help of these words.